Continuous presence of dinosauromorphs in South America throughout the Middle to the Late Triassic - Voltaire D. Paes Neto; Flávio A. Pretto; Agustín G. Martinelli; Francesco Battista; Maurício Garcia; Rodrigo T. Müller; Mauricio R. Schmitt; Tomaz P. Melo; Heitor Francischini; Cesar L. Schultz; Felipe Pinheiro; Marina B. Soares; et al. (Scientific Reports)
Abstract The dawn of dinosaurs is marked by the appearance of the saurischian lineages in the Late Triassic fossil record, around 230 million years ago. This early burst of diversification of the group is majoritarily represented by sauropodomorphs and herrerasaurids in late Carnian to early Norian of Brazil, Argentina, India, and Zimbabwe. However, “silesaurids”, an older and enigmatic group of quadrupedal dinosauromorphs, were recently found, in some works, as stem ornithischians. In this scenario, dinosaurs would have originated far earlier than the end of the Ladinian, a time in which “silesaurids” are already spread through Gondwana. Despite being also recorded in more recent dinosaur-bearing beds in Brazil, “silesaurids” are absent in strata from the early Carnian, an important time frame for dinosaur evolution. Here we present a new “silesaurid”, Itaguyra occulta gen. et sp. nov., that fills up the remaining gap of occurrence of these dinosauromorphs and provides new clues to the success of these putative early ornithischians.